2009
DOI: 10.1007/s11947-009-0297-5
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Plots for the Behavioral Pattern of Yersinia enterocolitica in Chocolate Milk as Affected by Trans-Cinnamaldehyde, a Spice Essential Oil Constituent

Abstract: Response surface plots were generated to determine the behavior of a native food isolate of Yersinia enterocolitica CFR 2301 in chocolate milk with added transcinnamaldehyde, an active spice essential oil constituent. The minimum inhibitory and bactericidal concentrations (MIC and MBC) for Y. enterocolitica in broth systems were 0.1 and 0.3 µl/ml, respectively, while in chocolate milk, the MBC was 0.9µl/ml. In chocolate milk devoid of cinnamaldehyde, the culture of Y. enterocolitica CFR 2301 was able to reach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Some authors noted that contact with animal manure and/or sick people or healthy carriers are the most important source of contamination. Numerous studies have highlighted the species Yersinia enterocolitica in surface water (rivers, lakes) and even in the depth, where it can survive longer because of the low concentration of toxic substances (Kattathara and Mandyam 2009).Also the incidence of Yersinia enterocolitica was much higher during winter than summer seasons (Toora et al,1989).These reasons explained this high result. The high incidence of Yersinia enterocolitica was also reported by Vidon and Delmas (1981).…”
Section: Results and Discuaaionmentioning
confidence: 99%
“…Some authors noted that contact with animal manure and/or sick people or healthy carriers are the most important source of contamination. Numerous studies have highlighted the species Yersinia enterocolitica in surface water (rivers, lakes) and even in the depth, where it can survive longer because of the low concentration of toxic substances (Kattathara and Mandyam 2009).Also the incidence of Yersinia enterocolitica was much higher during winter than summer seasons (Toora et al,1989).These reasons explained this high result. The high incidence of Yersinia enterocolitica was also reported by Vidon and Delmas (1981).…”
Section: Results and Discuaaionmentioning
confidence: 99%
“…Microbial safety has become a focal theme in the current scenario of food chain establishment and advanced detection methods have been evolved over the years [1,2]. Among the food borne pathogenic bacteria, Yersinia enterocolitica and related species are of public health concern, in that, being psychrophilic, they also exhibit a varied behavioral pattern to physical treatments, nonthermal processes, biopreservatives, micronutrients and bioactive spice constituents [3][4][5][6][7]. Although considered as a comparatively heat sensitive organism, research studies have indicated that heat sensitivity of Y. enterocolitica in culture systems and food matrices is affected by several factors such as temperature, medium composition, growth phase, conditions of heat treatment and physiology of the organisms [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%